Transformasi bank syariah: Peluang dan tantangan manajemen bank syariah pada masa Ibu Kota Nusantara - Aisyah, Dwi Danty (Maliki Interdisciplinary Journal, 2024)
Jakarta’s establishment as the capital city under Law Number 29 of 2007, has drawn public scrutiny towards the project of transferring the capital to East Kalimantan, termed the Nusantara Capital. This research focused on the opportunities and challenges that Islamic banks would face during the transition period. This investigation approach employs analysis from diverse entities including the reseach agency of Statistics or the Islamic Development Bank (IsDB). The outcomes of the descriptive study indicate that Islamic financial institutions must be mindful of both internal and external elements, along with geographical considerations, to effectively handle the economic uncertainties and obstacles encountered. The main challenges include increasing distance, state budget overruns, and tax increases. On the other hand, there are opportunities such as development financing policies, the vision of the IKN Economic Superhub, and cooperation with the Nusantara Capital Authority. With its vast populace, Islamic banking institutions have the opportunity for advancement in the Archipelago’s Principal City. In conclusion, the relocation of the capital city creates new dynamics for Islamic banking. With challenges to address and opportunities to seize, the future growth of the Islamic banking industry presents both hurdles and prospects.